Electrodeposited nickel cobalt manganese based mixed sulfide nanosheets for high performance supercapacitor application - Sahoo, S.; Mondal, R.; Late, D. J.; Rout, C. S. (Microporous and Mesoporous Materials, 2017)
Porous multi component Nickel Cobalt Manganese Sulfide (NCMS) nanosheets have been grown on Ni foam by cathodic electrodeposition method. The as-prepared NCMS nanosheets sample is used as an electrode material for supercapacitor application due to its large electrochemically active surface and high porosity structure. Moreover, NCMS nanosheets have good electrical and mechanical connections to the conductive Ni foam to achieve enhanced reaction kinetics with improved electrode integrity. The NCMS nanosheets exhibit an ultrahigh specific capacitance of 2717 Fig at a current density of 1 Aug with excellent cyclic stability and energy density of 94.07 Wh/kg. The electrodeposited NCMS nanosheets with extraordinary electrochemical performance enable the novel electrodes to hold great potential for high efficient energy storage systems.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, P. K. (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of α and β-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of β-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of α and β-NiMoO4 at a base pressure of ∼1 × 10−8 mbar. The obtained turn-on field at emission current density of 1 μA/cm2 for β-NiMoO4 nanosheets and α −NiMoO4 is 1.3 V/μm and 2.2 V/μm respectively were observed. The maximum field emission current density of 1.006 mA/cm2at an applied electric field of 2.7 V/μm was achieved for β-NiMoO4 nanosheets. Furthermore, we found that the β-NiMoO4 nanosheets possess good field emission performance compared to α-NiMoO4. The results indicate that NiMoO4can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase.
Keywords: Current stability; field emission; nanosheets; NiMoO4

Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.